2008
DOI: 10.1124/dmd.108.023325
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton Interruption in Human Hepatoma HepG2 Cells Induced by Ketamine Occurs Possibly through Suppression of Calcium Mobilization and Mitochondrial Function

Abstract: ABSTRACT:Ketamine is an intravenous anesthetic agent often used for inducing and maintaining anesthesia. Cytoskeletons contribute to the regulation of hepatocyte activity of drug biotransformation. In this study, we attempted to evaluate the effects of ketamine on F-actin and microtubular cytoskeletons in human hepatoma HepG2 cells and its possible molecular mechanisms. Exposure of HepG2 cells to ketamine at <100 M, which corresponds to clinically relevant concentrations for 1, 6, and 24 h, did not affect cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 40 publications
(53 reference statements)
2
22
0
Order By: Relevance
“…Further work is needed to analyze these distinct functions of ATP synthase in ketamine-treated embryos. In conclusion, the current findings are consistent with reported adverse effects of ketamine on the mitochondria and ATP production in human cells (Baker et al, 2016; Chang et al, 2009; Ito et al, 2015), dysfunctional cardiac function in infant non-human primates (Hotchkiss et al, 2007) and newborn human infants (Saarenmaa et al, 2001), additionally providing mechanistic data that show ALCAR as a protectant against these adverse effects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further work is needed to analyze these distinct functions of ATP synthase in ketamine-treated embryos. In conclusion, the current findings are consistent with reported adverse effects of ketamine on the mitochondria and ATP production in human cells (Baker et al, 2016; Chang et al, 2009; Ito et al, 2015), dysfunctional cardiac function in infant non-human primates (Hotchkiss et al, 2007) and newborn human infants (Saarenmaa et al, 2001), additionally providing mechanistic data that show ALCAR as a protectant against these adverse effects.…”
Section: Discussionsupporting
confidence: 91%
“…Ketamine led to mitochondrial dysfunction in neurons derived from human induced pluripotent stem cell (Ito et al, 2015) and acute ketamine administration has been shown to impair mitochondrial function in rat brains (Venancio et al, 2015). Ketamine suppresses ATP biosynthesis in HepG2 cells (Chang et al, 2009). However, the molecular mechanism of how ketamine causes mitochondrial dysfunction and suppresses ATP production is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have already investigated the relationship between F-actin and Ψ m in yeast and mammalian cells [56,57]. In yeast, a decrease in actin dynamics in certain actin mutants significantly reduced the mitochondrial membrane potential [58].…”
Section: Discussionmentioning
confidence: 99%
“…For imaging analyses of ZO-1 and occludin tight junctions, these 2 proteins were immunodetected using polyclonal antibodies against rabbit anti-ZO-1 and occludin (Zymed). A confocal laser scanning microscope (Model FV500, Olympus) was utilized to analyze the samples (28).…”
Section: Methodsmentioning
confidence: 99%